1988
DOI: 10.1182/blood.v71.3.748.748
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucose-6-phosphate dehydrogenase deficiency upon sickle cell anemia

Abstract: We studied the interactions of the A- variety of glucose-6-phosphate dehydrogenase (G6PD) deficiency and sickle cell anemia (HbSS) to see if G6PD deficiency influenced laboratory and clinical features of HbSS. A total of 801 male patients over age 2 had G6PD electrophoresis on cellulose acetate membranes. Assays of both G6PD activity and hexokinase activity were then done on all samples that had an electrophoretic pattern other than the normal wild type (GdB). The collection of clinical data used a standardize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Similarly, the transfusion rate was lower in the CSSCD cohort, with 35% of children being transfused before 5 years vs. 46% before 42 months for our study. The rates of infection and vaso-occlusive crisis were not significantly different between the two groups, in agreement with earlier data from cross-sectional studies (Bienzle et al, 1975;Gibbs et al, 1980;Steinberg et al, 1988;Bouanga et al, 1998;Nouraie et al, 2010). Despite that, G6PD-deficient patients had an almost 3-fold increase in blood transfusion requirement for both AAEs and vaso-occlusive or infectious events.…”
Section: á26supporting
confidence: 90%
See 2 more Smart Citations
“…Similarly, the transfusion rate was lower in the CSSCD cohort, with 35% of children being transfused before 5 years vs. 46% before 42 months for our study. The rates of infection and vaso-occlusive crisis were not significantly different between the two groups, in agreement with earlier data from cross-sectional studies (Bienzle et al, 1975;Gibbs et al, 1980;Steinberg et al, 1988;Bouanga et al, 1998;Nouraie et al, 2010). Despite that, G6PD-deficient patients had an almost 3-fold increase in blood transfusion requirement for both AAEs and vaso-occlusive or infectious events.…”
Section: á26supporting
confidence: 90%
“…Studies investigating potential effects of G6PD deficiency on the severity of SCA have produced conflicting results. Some studies found no effect of G6PD deficiency on the clinical manifestations, Hb levels, or reticulocyte counts of SCA patients (Gibbs et al, 1980;Steinberg et al, 1988), whereas others found lower Hb levels in patients having both diseases (Bouanga et al, 1998;Nouraie et al, 2010). In a study of transcranial Doppler ultrasonography (TCD) findings in a cohort of stroke-free SCA patients, G6PD deficiency was among the independent risk factors for high blood flow velocities, a finding predictive of stroke (Bernaudin et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strength of the association between G6PD and SCArelated morbidity is controversial. Previous studies (Steinberg et al, 1988) found no evidence that G6PD deficiency could increase the severity of haemolysis or the incidence of acute anaemic episodes in SCA.…”
Section: Cerebral Macrovasculopathy and Glucose-6-phosphate Dehydrogementioning
confidence: 81%
“…Summary of multivariate regressions of HbF on historical outcomes, adjusted for gender and age at enrollment. a-Thalassaemia 51% n/a n/a 62% 42% (Adekile et al, 2007) 38% 30% (Steinberg & Embury, 1986) G6PD deficiency 28% n/a n/a 21% 2Á5% 10% (Steinberg et al, 1988) SCD, sickle cell disease; G6PD, glucose-6-phosphate dehydrogenase; MCV, mean corpuscular volume; n/a, not reported or not applicable.…”
Section: Supporting Informationmentioning
confidence: 99%